Characterization, Dissolution, and Solubility of Zn-Substituted Hydroxylapatites [(ZnxCa1−x)5(PO4)3OH] at 25°C. (15th June 2017) - Zhao, Xin; Zhu, Yinian; Zhu, Zongqiang; Liang, Yanpeng; Niu, Yanlong; Lin, Ju
Abstract : A series of Zn-substituted hydroxylapatites [(Zn x Ca1− x )5 (PO4 )3 OH, Zn-Ca-HA] with the Zn/(Zn + Ca) molar ratio (X Z n ) of 0~0.16 was prepared and characterized, and then the dissolution of the synthesized solids in aqueous solution was investigated by batch experiment. The results indicated that the aqueous zinc, calcium, and phosphate concentrations greatly depended on the Zn/(Zn + Ca) molar ratio of the Zn-Ca-HA solids (X Z n ). For the Zn-Ca-HA dissolution at 25°C with an initial pH of 2.00, the final solution pH increased, while the final solution calcium and phosphate concentrations decreased with the increasing X Z n . The final solution zinc concentrations increased with the increasing X Z n when X Z n ≤ 0.08 and decreased with the increasing X Z n when X Z n = 0.08~0.16. The mean K s p values for (Zn x Ca1− x )5 (PO4 )3 OH at 25°C decreased from 10 −57.75 to 10 −58.59 with the increasing X Z n from 0.00 to 0.08 and then increased from 10 –58.59 to 10 –56.63 with the increasing X Z n from 0.08 to 0.16. This tendency was consistent with the dependency of the lattice parameter a on X Z n . The corresponding free energies of formation ( Δ G f o ) increased lineally from −6310.45 kJ/mol to −5979.39 kJ/mol with the increasing X Z n from 0.00 to 0.16.